Cultivating Hope Through Learning for the Common Good. Issue 5 (19th October 2016) - McEwen, Rhonda M.; Herman, Wayne R.; Himes, Brant M.
ABSTRACT: This article examines how an orientation toward hope can guide institutions of higher education in achieving their ultimate purpose of providing education for the common good of society. In today's cultural context, colleges and universities must navigate a multitude of challenges and competing philosophies, many of which question the validity of their inherent value and purpose. As society continues to press questions of market relevance, sustainability, accessibility, quality, and the value of higher education, a basic question remains: How, amid all of these challenges, can today's postsecondary institutions contribute to the cultivation of a better society? In this regard, faith-based colleges and universities can offer guidance. By carrying out their distinctive mandate of infusing their educational mission with the holistic character formation of students, these institutions can promote the common good by coupling the Gospel message of personal hope in Jesus Christ with the call to cultural influence and transformation. To demonstrate this concept, a framework is offered that describes both a starting point—a biblical foundation for understanding humanity and hope—and a pathway through learning. The application of this framework—uncommon learning for the common good—invites implications for curricular design, the facilitation of learning, and institutional leadership that faculty and administrators from across the spectrum of higher education may find timely and relevant to their own learning contexts.